Nutrient acquisition strategies augment growth in tropical N 2 ‐fixing trees in nutrient‐poor soil and under elevated CO 2 - Megan K. Nasto; Klaus Winter; Benjamin L. Turner; Cory C. Cleveland (Ecology, 2019)
Tropical forests play a dominant role in the global carbon (C) cycle, and models predict increases in tropical net primary productivity ( NPP ) and C storage in response to rising atmospheric carbon dioxide ( CO 2 ) concentrations. The extent to which increasing CO 2 will enhance NPP depends in part on the availability of nitrogen (N) and phosphorus (P) to support growth. Some tropical trees can potentially overcome nutrient limitation by acquiring N via symbiotic dinitrogen (N 2 ) fixation, which may provide a benefit in acquiring P via investment in N‐rich phosphatase enzymes or arbuscular mycorrhizal ( AM ) fungi. We conducted a seedling experiment to investigate the effects of elevated CO 2 and soil nutrient availability on the growth of two N 2 ‐fixing and two non‐N 2 ‐fixing tropical tree species. We hypothesized that under elevated CO 2 and at low nutrient availability (i.e., low N and P), N 2 fixers would have higher growth rates than non‐N 2 fixers because N 2 fixers have a greater capacity to acquire both N and P. We also hypothesized that differences in growth rates between N 2 fixers and non‐N 2 fixers would decline as nutrient availability increases because N 2 fixers no longer have an advantage in nutrient acquisition. We found that the N 2 fixers had higher growth rates than the non‐N 2 fixers under elevated CO 2 and at low nutrient availability, and that the difference in growth rates between the N 2 and non‐N 2 fixers declined as nutrient availability increased, irrespective of CO 2 . Overall, N 2 fixation, root phosphatase activity, and AM colonization decreased with increasing nutrient availability, and increased under elevated CO 2 at low nutrient availability. Further, AM colonization was positively related to the growth of the non‐N 2 fixers, whereas both N 2 fixation and root phosphatase activity were positively related to the growth of the N 2 fixers. Though our results indicate all four tree species have the capacity to up‐ or down‐regulate nutrient acquisition to meet their stoichiometric demands, the greater capacity for the N 2 fixers to acquire both N and P may enable them to overcome nutritional constraints to NPP under elevated CO 2 , with implications for the response of tropical forests to future environmental change.